Effects of pulverized fuel ash as cement replacement material toward concrete microstructure - Nor Liyana , Suraini (2012)
The Pulverized Fuel Ash (PFA) is known as pozzolanic material and can be used as cement replacement material in the concrete in order to improve concrete properties. The use of PFA in concrete manufacture has reduced the disposal issue and can reduce cement consumption which is cut down the emission of the carbon dioxide, CO2 as well as to reduce environmental problem caused by production of cement. This study has designed to determine the potential of PFA as cement replacement material in concrete, which are to determine the effectiveness of PFA toward compressive strength and its effect to concrete microstructure. X-ray Diffraction (XRD) and Scanning Electron Microscope (SEM) were used to study the concrete microstructure development base on concrete age and curing period. The result of compressive strength indicates the optimum percentage of PFA as cement replacement is about 20% has increased the strength of concrete. The XRD and SEM have shown concrete with different percentage of PFA produced different intensity of C-S-H. It were shown that, the replacement of PFA as cement replacement can contribute to the different properties of concrete that can lead to concrete quality improvement. As conclusion, the PFA has the potential to be used as a cement replacement material in concrete because it will increase the strength and durability of concrete by improving the structure of the microstructure. However, the percentage of its replacement should be set and monitor to avoid a reduction in the level of quality required.